Evaluation of Banana Varieties through Farmer’s Participatory Selection at Teppi, Southwestern Ethiopia - Sora, Shamil Alo; Getahun, Betelhem (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Participatory varietal selection was conducted in Southwestern part of Ethiopia to evaluate the performance of banana cultivars and to identify farmers’ preference and selection criteria in the study area. Seven banana cultivars collected from Melkassa agricultural research center were evaluated in single plot in 2020-2023 main cropping season. Farmers’ evaluation was made at two different stages of the crop, namely at vegetative and at maturity using both direct-matrix and pair-wise ranking methods of selection scheme. Farmers’ set; plant height, disease resistance/tolerance, fruit size and yield as selection criteria to evaluate and identify their preferred cultivars. The results of analysis of variance indicated the existence of highly significant differences among cultivars for all traits measured at 5% probability level. From the previous experiments, the highest mean yield was obtained from the cultivar William I (45.32 t/ha), Dinke-1 (45.1 t/ha), Lady Finger (40.16 t/ha) and Poyo (40 t/ha). Likewise, these three cultivars (William, Dinke-1, and Lady Finger) were identified as farmers preferred cultivars from both pair-wise and direct matrix ranking evaluations. Thus, these cultivars were chosen for their performance in the field and from farmers' evaluation perspective. Moreover, this study indicated participatory varietal selection is a viable method to gain greater insight into farmers’ perceptions, preferences, merits and shortcomings of banana cultivars. Therefore, based on the results of this study, William I, Dinke-1 and Lady Finger cultivars are recommended for multiplication and distribution to farmers in the area and similar agro-ecologies.